Características epidemiológicas de la enfermedad renal crónica terminal en la UMAA-UMF 75 de Morelia Michoacán - Ramírez Valencia, Jorge (Universidad Michoacana de San Nicolás de Hidalgo, 2018)
Chronic kidney disease (CKD) is the result of many chronic degenerative diseases, among which are type 2 diabetes (T2D) and hypertension (HTA), phenomenon that occurs similarly in the whole world and that unfortunately leads to fatal if untreated OBJECTIVE: Knowing what the epidemiological situation of people with ESKD treated at the Nephrology Service of the UMAA-UMF No.75, Morelia, Michoacán. MATERIAL AND METHODS: Retrospective, crosstabs, descriptive study in the UMAA-UMF No. 75 reviewing the medical records of patients diagnosed with ESKD, attending the module dialysis and hemodialysis. Type of replacement therapy in renal function is investigated, cause kidney damage, comorbidities, treatment time, place of origin, biochemical markers, peritonitis, etiology of peritonitis, and hemodialysis dose. Descriptive and inferential statistics were used. RESULTS: We studied 436 patients, both sexes; 231 in DPCA, 102 in DPA and 13 in HD. 233 of the municipality of Morelia, followed by the municipalities of the eastern state of Michoacán. The etiology is DM, hypertension arterial, hypoplasia and unknown cause. It is a pathology of poverty. Age <30 years in eastern Michoacán is a risk factor for the development of ESRD (OR = 3.696, 95% CI 2.565-5.326, p <0.0001). CONCLUSIONS: The CKD is a public health problem that affects the poor population; its etiology is DM2, hypertension, followed by renal hypoplasia and of unknown cause; the young population of eastern Michoacán state seems to have a greater risk of developing it. Additional studies are required to confirm this hypothesis and systematize existing information.

La enfermedad renal crónica es la resultante de enfermedades crónico degenerativas, entre las que destacan diabetes mellitus e hipertensión arterial, fenómeno que ocurre de manera similar en todo el mundo y que, conduce hacia un desenlace fatal si no es tratada. OBJETIVO: Caracterizar el panorama epidemiológico de la población con ERCT atendida en el servicio de Nefrología de la UMAA-UMF No.75 en Morelia, Michoacán. MATERIAL Y METODOS: Estudio retrospectivo, transversal, descriptivo, se realizó la revisión de los expedientes clínicos de los pacientes con diagnóstico de ERCT, que acuden al módulo de diálisis. Se investigó, tipo de tratamiento sustitutivo de la función renal, causa del daño renal, comorbilidades, tiempo de tratamiento, lugar de procedencia, marcadores bioquímicos, presencia de peritonitis, y dosis de hemodiálisis. Se utilizó estadística descriptiva e inferencial. RESULTADOS: Se estudiaron 436 pacientes ambos sexos; 231 en DPCA, 102 en DPA y 13 en HD. 233 del municipio de Morelia, seguido de los municipios del oriente del estado de Michoacán. La etiología es DM2 seguida de HTA, hipoplasia renal y causa desconocida. Es una patología de la pobreza. La edad <30 años en el oriente de Michoacán es un factor de riesgo para el desarrollo de ERCT (OR= 3.696, IC95% 2.565-5.326, p<0.0001). CONCLUSIONES: La ERC es un problema de salud pública que afecta a la población de escasos recursos; su etiología es la DM2, HTA seguida de hipoplasia renal y de causa desconocida; la población joven del oriente del estado de Michoacán parece tener un mayor riesgo de desarrollarla.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4305; info:eu-repo/classification/cti/3; FCMB-E-2018-0300; Tratamiento sustitutivo; Epidemiología; Comorbilidades